Tensile strength of circular hollow sections with squashed ends. (1st May 2021) - Dundu, M.
Highlights: Flat-ended circular hollow sections were tested in tension. Three bolt configurations were established in flattened ends. Bearing failure and net-section fracture were observed. The test load increased with increase in the number of bolts. An adjusted bearing coefficient is suggested for bearing. Abstract: Experiments were performed to investigate the behaviour of 28 circular hollow sections (CHSs) in tension, with flat ends and three bolt configurations (2, 3 and 4 bolts). The length of the members between the flat ends was kept constant at 1500 mm for all CHSs, and the sizes of the sections ranged from 60.3x2.0 to 101.6x4.5. Two modes of failure were observed, viz; bearing failure (BF) and net-section fracture (NSF). CHSs connected with 2 bolts failed in bearing, whilst net-section fracture was dominant in sections with 3 and 4 bolts. The notion that the change in the number of bolts can lead to different behaviours of the connections is a significant contribution to knowledge, particularly if flat-ended CHSs are used as structural truss elements. This paper demonstrates that the sections are capable of supporting large loads, however, the capacity of the tested specimen did not reach the full yield strength. It is apparent from the tensile strengths that a larger increase in strength was accomplished when the number of bolts was increased from 2 to 3 bolts than from 3 to 4 bolts. A comparison of the tensile strength with the strengths predicted by the North American standard (AISI S100-16w/S1-18), Australia/New Zealand standard (AS/NZS-4600:2018) and European standard (EN 1993–1-3) confirm that both standards provides a reasonable assessment of the strength of the 3 and 4 bolt configuration, which failed purely by net-section fracture. However, for the 2-bolted connections, which failed in bearing, it is proposed to use AS/NZS 4600:2018, with a bearing coefficient of C = 2.85, instead of C = 3.0, to increase the accuracy of the bearing strength expression for these specimens.